KUALITAS ARANG AKTIF DARI 5 JENIS KAYU (Activated charcoal quality from 5 wood species) - Gustan Pari (Jurnal Penelitian Hasil Hutan, 1996)
Experimental study on several HTI wood species to produce activated charcoal is reported in this paper. The result showed that the yield  of activated charcoal range from 30,35  - 43,25 %,  moisture content from 9,23 - 13,34  %, ash content from 1,62  - 6,76 %, volatile matter from 4,94 - 6,65%, fixed  carbon from  88,30-   91,73   %, adsorptive capacity of iodine from 1002 - 1130 mg/g and adsorptive  capacity  of benzene from 33,50 - 44,02 %. Based on adsorptive capacity of iodine, good  quality  of  the  activated  charcoal  was produce from  sengon  (Paraserienthes falcataria) wood species, this  criteria  has  met the commercial standard  requirement of  the Indonesian Industrial Standard and Japanese Standard.The quality  of  the cajeput oil refined with the good quality of activated charcoal experiment shows that the cineol content became 23,17  % from,21,76  %.Key words :  HTI timbers, Activated charcoal, Properties, Quality